How Ziglar v. Abbasi Sheds Light on Qualified-Immunity Doctrine - Hannah Beard (Washington University Law Review, 2019)
In 2011, a man was involved in a road rage incident on a public highway in New Mexico. Two women called 911 to report the man as a drunk driver who was swerving while driving. The women then drove close behind the man, keeping on their bright lights, until the man, feeling threatened, pulled over on the off-ramp of the highway. The man spoke with the women and asked them why they were following him. There was no physical altercation or violence. The man then left the off-ramp and drove to his house where he lived with his brother. Around 10:00 p.m., an officer responding to the women’s 911 call arrived at the off-ramp and interviewed the two women. The women gave the officer the man’s license plate number, and the women then left. Two other officers joined the interviewing officer on the off-ramp, and the three decided to investigate, though they decided that there was insufficient probable cause to arrest the man. One of the officers stayed on the off-ramp in case the man returned. The other two officers drove in separate police cars to the address registered with the license plate, and neither officer turned on his vehicle’s police lights. Arriving at the man’s rural, secluded house, each officer parked his car at a distance not visible from the house and covertly approached the residence. The officers used their flashlights intermittently. The officers saw a light on inside the house and the man and his brother moving around inside. Around 11:00 p.m., noticing that there were people outside using flashlights, the man and his brother yelled out, “Who are you?” and “What do you want?” to which the officers responded, “Hey motherfuckers, we got you surrounded. Come out or we’re coming in.” The man and his brother did not hear the officers identify themselves as police at any point, and they did not see any police vehicles. They believed that they were being attacked, perhaps because of the earlier road rage incident. At that point, the man’s brother yelled, “we have guns,” opened a side door, and fired two shotgun shots into the air to try to scare off the potential attackers. Meanwhile, the third officer arrived on the scene and covertly approached the house. He heard the “we have guns” statement, followed by the shots, and feared for his and his co-officers’ safety. One of the officers shot at the brother and missed. The third officer then shot at the brother and killed him. In White v. Pauly, from which the above facts are based, the brother’s estate sued the three officers for Fourth Amendment excessive force violations, and the officers moved for summary judgment asserting the defense of qualified immunity. A government official is entitled to qualified immunity when the official’s conduct “does not violate clearly established statutory or constitutional rights of which a reasonable person would have known.” The Supreme Court in White v. Pauly suggested that the third officer’s conduct did not violate clearly established law and remanded the case to the Tenth Circuit. The Tenth Circuit found that the officer who shot the brother was entitled to qualified immunity. The court granted the defendant’s motion for summary judgment against the plaintiff’s constitutional claim, holding that the officer did not violate clearly established law because the court could not identify any case “close enough on point to make the unlawfulness of [the officer’s] action apparent.” The purpose of qualified immunity is to allow law enforcement officers and government officials room to breathe in performing their duties so that they may make “reasonable but mistaken judgments about open legal questions” without fear of suit. There is a fundamental tension in qualified-immunity cases between the societal need for officers to be able to exercise discretion without fear of suit on the one hand, and, on the other hand, the constitutional and statutory rights of citizens. In the last three decades, however, qualified immunity has expanded incredibly, creating an almost insurmountable hurdle for civil rights plaintiffs. While there are many historical reasons for the expansion of qualified immunity, this Note examines the current state of the qualified-immunity doctrine, focusing specifically on the analytical procedure used by courts to decide qualified-immunity cases. In 2001, the Supreme Court held that lower courts ruling on qualified-immunity cases were required to decide both prongs of the qualified-immunity inquiry—i.e., courts were required to decide both (1) whether the official’s conduct would amount to a constitutional or statutory violation, and (2) whether the relevant law at the time of the official’s conduct was clearly established. In 2009, in Pearson v. Callahan, the Supreme Court overturned Saucier’s rule of mandatory sequencing after just eight years of its controversial application in qualified-immunity cases. The Pearson Court held, instead, that in deciding qualified-immunity cases courts now need only to decide the clearly-established prong of the qualified-immunity two-part inquiry. Under Pearson, if a court finds that the law was not clearly established at the time of the official’s conduct, the court has discretion whether or not to decide the underlying merits of the plaintiff’s claim. This Note proposes a new four-part balancing test which courts should use in choosing whether to decide both prongs of the qualified-immunity analysis, as in Saucier, or to decide only the clearly-established prong, as in Pearson. Part I traces the history and development of the Court’s qualified-immunity jurisprudence in order to shed light on the order-of-battle dilemma. Part II explains the empirical effects of Pearson on plaintiffs’ efforts to vindicate their civil rights. Part III focuses on the Supreme Court’s recent employment of Pearson discretion in Ziglar v. Abbasi to highlight four important concerns of qualified-immunity doctrine and to propose a new balancing test for the employment of Pearson discretion. The goal of this Note is to give courts a more nuanced standard for when to employ Pearson discretion, thus allowing vindication of plaintiffs’ rights while respecting the importance of the qualified-immunity defense for government officials.
Keywords: Qualified immunity; Constitutional law; Law enforcement; Ziglar v. Abbasi; Civil rights law; Excessive force